The impact of digital financial inclusion on economic growth in ASEAN countries – Policy implications for Vietnam - To, Thi Hong Gam; Tran, Thi Kim Oanh; Nguyen, Viet Hong Anh; Le, Ngoc Dung; Phan, Thi My Ca (Journal of Finance - Marketing Research, 2024)
Applying the Bayesian approach, this paper examines how digital financial inclusion affects economic growth in ASEAN nations between 2015 and 2022. The findings demonstrate that digital financial inclusion has a detrimental effect on economic growth. This is a significantly different conclusion from earlier research. This can be explained by the fact that digital financial services are still expensive and require a while to mature or adapt to current development paradigms. On the part of control factors, while unemployment (UNE) negatively affects economic growth, others including population growth (POP), inflation (INF), and foreign direct investment (FDI) have a positive effect. The authors used the research results on the data range of ASEAN countries as prior information to regress the model with the data range of Vietnam. The research model’s findings in Vietnam are quite similar to those of the research model in ASEAN countries in general except for the POP variable, which assumes that economic growth (GDP) will decrease when POP increases. Consequently, to stimulate economic growth, ASEAN nations, particularly Vietnam, must identify strategies to lower the cost of accessing digital finance, decrease the unemployment rate, attract more foreign direct investment, and sustain a moderate inflation rate. To reduce the cost of accessing digital finance, policymakers should encourage financial institutions to provide services at lower costs and in remote areas. Additionally, FinTech providers can be leveraged to provide digital financial services.